2022
DOI: 10.1186/s12889-022-14311-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational characteristics associated with SARS-CoV-2 infection in the UK Biobank during August–November 2020: a cohort study

Abstract: Background Occupational exposures may play a key role in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection risk. We used a job-exposure matrix linked to the UK Biobank to measure occupational characteristics and estimate associations with a positive SARS-CoV-2 test. Methods People reporting job titles at their baseline interview in England who were < 65 years of age in 2020 were included. Healthcare workers were excluded bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The minimally adjusted analyses showed that occupational exposures are associated with a positive test, which is in line with previous research on occupational exposure and COVID-19 infections ( 31 33 ). After correcting for other factors including children living at home and residence area, occupational exposure to Sars-Cov-2 still elevated the risk to be infected but became smaller for all dimensions and across all pandemic waves.…”
Section: Discussionsupporting
confidence: 89%
“…The minimally adjusted analyses showed that occupational exposures are associated with a positive test, which is in line with previous research on occupational exposure and COVID-19 infections ( 31 33 ). After correcting for other factors including children living at home and residence area, occupational exposure to Sars-Cov-2 still elevated the risk to be infected but became smaller for all dimensions and across all pandemic waves.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study that applied the British version of the international JEM, associations were noted between SARS-CoV-2 infection and the number of contacts and social distancing, and the authors observed that in three domains -number, nature of contacts, and social distancing -there was an exposure-response relationship between the exposure levels and risk of SARS-CoV-2 infection (26). In a British study that applied the O*NET-based JEM, frequent occupational exposure to disease/infections and working in close proximity with others were associated with increased risk for a positive SARS-CoV-2 test (27). Taken together, our results and those of previous studies support the reasonable conclusion that close physical proximity in the workplace and contacts with infected/diseased persons/patients increase the risks for a positive test for SARS-CoV-2 and the clinical disease of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that applied the British version of the international JEM, associations were noted between SARS-CoV-2 infection and the number of contacts and social distancing, and the authors observed that in three domains – number, nature of contacts, and social distancing – there was an exposure–response relationship between the exposure levels and risk of SARS-CoV-2 infection ( 26 ). In a British study that applied the O*NET-based JEM, frequent occupational exposure to disease/infections and working in close proximity with others were associated with increased risk for a positive SARS-CoV-2 test ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a more significant risk of COVID-19 infection among critical professionals, particularly those in social and educational fields [24]. Furthermore, Yanik et al studied occupational characteristics correlated with COVID-19 infection among people in the United Kingdom and discovered that the probability of COVID-19 infection was higher in jobs that did not allow for remote work [25].…”
Section: Discussionmentioning
confidence: 99%